Optimizing Digital Integrated Care via Micro‐Randomized Trials. Issue 1 (19th April 2018) - Walton, Ashley; Nahum‐Shani, Inbal; Crosby, Lori; Klasnja, Predrag; Murphy, Susan
Abstract : Mobile health (mHealth) interventions are a promising tool in providing digitally mediated integrative care. They can extend care outside of the clinic by providing reminders to take medications, assisting in managing symptoms, and supporting healthy behaviors including physical activity, healthy eating, and stress management. mHealth interventions can adapt the delivery of care across time in order to optimize treatment effectiveness. Yet there exists limited empirical evidence useful to the development of adaptive mHealth interventions. This article describes a new randomized trial design, the Micro‐Randomized Trial (MRT), for informing the development of mHealth interventions. We provide examples of scientific questions important to the development of an mHealth intervention, and describe how these questions can be answered using an MRT.